Unified numerical process modeling of forming and consolidation for thermoplastic composites with prepreg patches - Mulye, P. D.; Morançay, L.; Binetruy, C.; Comas-Cardona, S.; Leygue, A.; Guillon, D. (Frontiers in Materials, 2023)
The main idea behind “Quilted Stratum Process” (QSP® ) is to create a flat blank made of unidirectional/woven thermoplastic prepreg patches instead of using uniformly shaped prepreg stack as is the case with standard thermostamping process. Thus, using QSP® ; one can manufacture components with complex geometries by using nearly rectangular patches while still maintaining a short cycle time similar to the standard thermostamping process. The use of near- rectangular patches results in a significant material saving which is a necessity for a sustainable product development. During standard thermostamping and/or QSP® ; the consolidation phase plays a key role in the strength and quality of the final product. This becomes even more important in the case of unidirectional thermoplastic prepregs where mechanisms such as transverse squeeze flow can impact not only the in-plane dimensions of the prepreg but also the fibre orientations within the prepreg. This work presents a unified modeling approach that combines a novel pinching shell element, a new elasto-plastic constitutive model for pinching shell in order to provide a unified solution to simulate both forming and consolidation-flow using a shell-based approach. This unique unified approach of simulating forming and consolidation provides a set of additional outputs such as the through-thickness stress, final deformed shape of the plies including the squeeze flow effect and the changes in the orientation of fibres within the plies during and after the process. This work finally demonstrates how this information can help the manufacturers to design better tooling based on the outcomes of the numerical process simulation in order to achieve a desired product quality. Additionally, one can also steer the final fibre orientation which results from the initial position of the patch, its forming and squeeze flow.